Study on Apoptosis of Prostate Cancer Cells Induced by IκBα Overexpression Synergistic with Poly (Lactic-Co-Glycolic Acid)-Curcumin Nanoparticles - Hui Guo; Jianwen Huang; Hongbin Li; Ranxing Yang; Rong Chen (Advances in Materials Science and Engineering)
Objective. To investigate the synergistic effects of IκBα overexpression and poly (lactic-co-glycolic acid)-curcumin nanoparticles (PLGA-Cur-NPs) on prostate cancer (PC) and reveal the underlying mechanisms of cooperative sensitization induced by curcumin. Methods. Proliferation and apoptosis rate in IκBα overexpressed and PLGA-Cur-NPs-treated PC cells were detected by MTT and flow cytometry assay. The expression levels of IκBα, apoptosis-related, and signaling proteins were measured by western blotting assay. Results. PC cell proliferation was significantly inhibited by the overexpression of IκBα. The apoptosis rate of PC cells was significantly increased at a high concentration of curcumin exposure, while the activation of NF-κB pathway was obviously inhibited. In addition, PLGA-Cur-NPs treatment synergistic with IκBα overexpression enhanced the apoptosis of PC cells by suppressing the NF-κB pathway activation. Conclusion. IκBα overexpression synergistic with PLGA-Cur-NPs could obviously inhibit proliferation, induce apoptosis, and suppress the activation of NF-κB pathway in PC cells. These findings may provide an experimental basis to establish the tumor gene therapy combined with traditional Chinese medicine treatment, thus promoting the clinical application of both tumor gene therapy and anti-tumor Chinese medicine.